Bite force and occlusal stress production in hominin evolution. Issue 4 (11th June 2013) - Eng, Carolyn M.; Lieberman, Daniel E.; Zink, Katherine D.; Peters, Michael A.
ABSTRACT Maximum bite force affects craniofacial morphology and an organism's ability to break down foods with different material properties. Humans are generally believed to produce low bite forces and spend less time chewing compared with other apes because advances in mechanical and thermal food processing techniques alter food material properties in such a way as to reduce overall masticatory effort. However, when hominins began regularly consuming mechanically processed or cooked diets is not known. Here, we apply a model for estimating maximum bite forces and stresses at the second molar in modern human, nonhuman primate, and hominin skulls that incorporates skeletal data along with species‐specific estimates of jaw muscle architecture. The model, which reliably estimates bite forces, shows a significant relationship between second molar bite force and second molar area across species but does not confirm our hypothesis of isometry. Specimens in the genus Homo fall below the regression line describing the relationship between bite force and molar area for nonhuman anthropoids and australopiths. These results suggest that Homo species generate maximum bite forces below those predicted based on scaling among australopiths and nonhuman primates. Because this decline occurred before evidence for cooking, we hypothesize that selection for lower bite force production was likely made possible by an increased reliance on nonthermal food processing. However, given substantial variability among in vivo bite force magnitudes measured in humans, environmental effects, especially variations in food mechanical properties, may also be a factor. The results also suggest that australopiths had ape‐like bite force capabilities. Am J Phys Anthropol 151:544–557, 2013. © 2013 Wiley Periodicals, Inc.